2015
DOI: 10.7314/apjcp.2015.16.10.4353
|View full text |Cite
|
Sign up to set email alerts
|

High Efficacy of Levofloxacin-Dexlansoprazole-Based Quadruple Therapy as a First Line Treatment for Helicobacter pylori Eradication in Thailand

Abstract: Background: Levofloxacin is an effective medication for second line Helicobacter pylori (H. pylori) eradication. However, limited studies have approved its use as an effective antibiotic in first line therapy. Dexlansoprazole is a new PPI and lacks of evidence in support of a role in H. pylori eradication. This study was designed to evaluate efficacy of levofloxacin-dexlansoprazole-based quadruple therapy for H. pylori eradication in Thailand. Materials and Methods: This prospective randomized control study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“… We previously showed that genotype RM was the most common genotype in Thailand. Rabeprazole has no significant effects on most cytochrome P450 enzyme systems and may be one of the preferred PPIs in areas where the prevalence of PPI rapid metabolizers is high. In this study, the prevalence of CYP2C19 genotype was similar among study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… We previously showed that genotype RM was the most common genotype in Thailand. Rabeprazole has no significant effects on most cytochrome P450 enzyme systems and may be one of the preferred PPIs in areas where the prevalence of PPI rapid metabolizers is high. In this study, the prevalence of CYP2C19 genotype was similar among study groups.…”
Section: Discussionmentioning
confidence: 99%
“… The global eradication rate of standard triple regimen for H pylori infection has declined to where it is no longer recommended as an empiric choice in most countries. In some regions, levofloxacin‐containing triple or quadruple therapies have proved successful for H pylori eradication but the rapid increase in fluoroquinolone resistance has begun to limit fluoroquinolone use . Successful therapy depends on many factors including adherence, antibiotic resistance, dose of proton‐pump inhibitor (PPI), and duration of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroquinolone such as levofloxacin and moxifloxacin, was introduced to be effective drugs for treating H. pylori infection. However, fluoroquinolone resistance is now a growing problem and impact on the eradication rate in many countries (Vilaichone et al, 2013;Prapitpaiboon et al, 2015). H. pylori resistance to clarithromycin and fluoroquinolone was related with mutation points that can be tested by molecular technique.…”
Section: Introductionmentioning
confidence: 99%
“…This regimen could be used as an alternative first line therapy for H. pylori eradication. Dexlansoprazole appears to be effective in improving heartburn, regurgitation and maintained for the duration of the treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that early detection, timely and effectively take antibiotics could prevent and control upper digestive system diseases to a great extent. Years past H. pylori has been found to be a bacteria which is difficult to treat, and it also obtained the resistance of common used antibiotics [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%